ANALISA PENGARUH PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KARTU SELULER SIMPATI PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS WARMADEWA - Ni Putu Andini Desiyanti Laksmi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
The number of cellular providers in Indonesia are mutually price war with a variety of advantages each resulting in confusion in selecting society. This study aims to determine the effect of product, price and promotion either partially or simultaneously, and to determine the most dominant influence in influencing consumer purchasing decisions. This type of research is included in the survey research. The sample used in this research is 96 students of Economics faculty at Univercity Warmadewa, where the sample is taken by using accidental sampling technique. Collection was done by distributing questionnaires. Data analysis techniques used are Multiple Linear Regression Analysis, Correlation Analysis, Coefficient of Determination and Test F and Test t. The results of this study showed the value of multiple linear regression analysis that is Y = 0.426 + 0.274 X1 + 0,152 X2 + 0,453 X3 value of coefficient of determination show value equal to 0,689. This shows that in consumer satisfaction variable shows 68,9% value influenced by product, price and promotion variable. While the remaining 31.1% influenced by other variables not included in this study. Test F obtained result that Product (X1), Price (X2), and Promotion (X3) have influence to Decision of Simpati (Y) cellular card, sig value. F 0,000 (<0.05), then H0 is rejected and H1 is accepted. The conclusion is that all independent variables (Product variables (X1), Price (X2), and Promotion (X3)) have significant effect simultaneously on Simpati Mobile Card Purchase Decision (Y). The value of the product thitungvariable (X1) has a value of 3.634 and the value of Sig. 0.000 <0,05, then Ho is rejected and H1 accepted, it means there is partial influence by Product variable (X1) to Purchase Decision (Y). Price Variable (X2) has Thitung3.067 and Sig value. 0,003 <0,05, then Ho is rejected and H1 is accepted, that means there is partial influence by Price variable (X2) to Purchase Decision (Y) .Variable Promotion (X3) has value of Thitung 6,222 and Sig value. of 0.000 <0.05, then Ho is rejected and H1diterima, it means there is a partial influence by the variable Promotion (X3) on Purchase Decision (Y) In addition, the results of this study also shows that Product, Price, and Promotion has a dominant influence on the decision purchase of Simpati cellular card at Univercity Warmadewa. .